Pelatihan Bim dan Microsoft Project sebagai Upaya Peningkatan Kompetensi Bidang Konstruksi Guru SMK di Kota Surabaya - Wahyu Dwi Mulyono; Gde Agus Yudha Prawira Adistana; Suprapto Suprapto (JURPIKAT, 2026)
The rapid development of technology has become a global challenge in the 21st century. As the century of industrial revolution 4.0 and 5.0 many changes in lifestyle and work. These changes triggered changes in the world of work. Vocational High Schools must adapt to these changes. This program aims to improve the skills of teachers in using Building Information Modeling (BIM) with Autodesk Revit software and project management skills with Microsoft Project software. This partner is the Surabaya City Construction and Property Technology Subject Teachers Council (MGMP). The program implementation is divided into three parts: the development of job sheets and video tutorials, Autodesk Revit training, and Microsoft Project training. The results obtained from this PKM program are as follows. (1) Job sheets and video tutorials for Autodesk Revit and Microsoft Project, (2) improving teachers' skills in using Autodesk Revit, and (3) improving teachers' skills in using Microsoft Project.